ON TWO TYPES OF METALLIFEROUS CARBONACEOUS ROCKS - Tomson I.N.; Polyakova O.P.; Alekseev V.Yu.; Baskina V.A. (My University, 2006)
Two types of metalliferous carbonaceous rocks that differ in associated metals are considered. One of them is characterized by gold occurring in finely dispersed arsenopyrite and arsenic-bearing pyrite, and the other, by finely impregnated native metals in carbonaceous matter. Rocks of the first type also contain elements of the platinum group, while those of the second type bear rhenium, silver, iron, molybdenum, and other metals. Graphitic mineralization is usually localized in the shear zone associated with alkaline basalts. © Pleiades Publishing, Inc., 2006.